Uso de vermicomposto na atenuação do efeito do cobre em planta de Avena strigosa Schreb - Cantoni, Fernanda (2018)
The application of copper-based fungicides are frequently realized in order to perform the preventive control of fungal diseases. Nonetheless, the long term application causes a surplus of this heavy metal in soil. Thus, this study aimed to characterize the effects of vermicompost on growth and development of the ground cover plant Avena strigosa in sandy soils with surplus of copper from vineyards. The experiment was carried out in a greenhouse and the soil samples were collected in a vineyard in Santana do Livramento, in the Campanha Gaúcha region. A 50 mg kg-1 dosage of copper was added on the sampled soil, and designing seven treatments: 0 (V0), 25 (V25), 50 (V50), 100 (V100) e 200 (V200) kg ha -1 of Nitrogen (N) via vermicompost of bovine manure, and also a treatment with mineral fertilizer (AM). The first day of experiment set up a forced leaching on soil was realized and the leached was collected, thereafter, the sampling were realized each 15 days. On the leachate, the levels of Cu, Zn, Fe, Mn, P and pH of all samples were evaluated. In the soil, the availability of Cu, P, K, Mg, Fe and Zn was determined, and also on aerial part and root the accumulation of Cu, P, K, Mg, Fe and Zn was determined, the dry mass of aerial part of black oat. The enzyme activity of oxidative stress were evaluated by 52 days of experiment. In higher doses of vermicompost a bigger production of the dry mass of aerial and root parts, as well as higher levels of N, P and K, and lower levels of Cu, Zn, Fe and Mn were determined. Additionally, with higher doses of vermicompost a higher leaching of Cu and P was observed. The addition of vermicompost showed effective on the reduction of the phyto-toxicity of Cu. Thus, the black oat has potential to be used in the remediation of copper in combination with bovine manure based vermicompost, additionally this combination has the potential to reduce the leaching of copper and phosphorus.